Effect of pool length on blood lactate, heart rate, and velocity in swimming - Keskinen, O. P.; Keskinen, K. L.; Mero, A. A. (International Journal of Sports Medicine, 2007)
Exercise testing in water has been used to follow the progression of conditioning during regular training in swimmers. The present study examined the effects of pool length in eleven male swimmers on a set of 5 × 200-m freestyle swims with increasing speed from submaximal to maximal. Mean velocity of swimming, blood lactate and heart rate were examined in both 25-m and 50-m pools. Turning benefit as a marker for turning skill was measured separately by a underwater video system (speed difference between pre- and post-turning) during short all-out swims. Maximum force during swimming was measured in tethered swimming and explosive strength of leg extensor muscles was evaluated by a counter movement jump. The significantly higher (p = 0.033 - 0.000) blood lactate values for the 50-m pool as compared to the 25-m pool were found at each point of swimming velocity versus blood lactate curve. The highest post-test lactate level was 7.36 ± 1.47 mmol · l-1 in the short course and 8.24 ± 1.55 mmol · l-1 (p = 0.033) in the long course. The maximum swimming velocity was significantly greater (4.5 %) in the 25-m pool swimming (1.38 ± 0.11 m · s-1 vs. 1.32 ± 0.12 m · s-1; p = 0.000). The heart rate values were significantly (p = 0.020 - 0.000) lower in the short course than in the long course at all points of submaximal velocity with a mean difference of 7.3 ± 0.7 bpm. Heart rate was equal (172 ± 14 vs. 172 ± 14 bpm) after the maximum swims in both short and long course. The turning benefit in the short maximum swim was 0.12 ± 0.05 m · s-1 (8.1 ± 3.2 %), correlating positively with the difference in maximal swimming velocity between the short and long-pool swims (r = 0.59; p = 0.029), with the maximum force during tethered swimming (r = 0.75; p = 0.004) and with the vertical jumping height in the counter movement jump (r = 0.55; p = 0.039). We conclude that the pool length has a strong effect on blood lactate concentration and heart rate with greater swimming velocity in the short course pool.